The Evolutionary Effect of Syrian Asylum Seekers on Space: A Case Study of Gaziantep City - Türkoğlu, Emrah; Elmastaş, Necmettin (Fırat University, 2023)
Turkey-Syria relations, which started to normalize with the 1998 Adana Agreement, reached the best position in history after Bashar Assad came to power after 2000. But the process called "Arab spring or Damascus spring" both interrupted Turkey-Syria diplomacy and dragged Syria into civil war. As a result, the process that turns the Syrian population into refugees in other countries has begun. Turkey ranks first among the countries most preferred by Syrians in the migration process. The main reason for this is the strong historical ties between Turkey and Syria. In general, Turkey, in particular Gaziantep, has turned into densely populated places with the migration of Syrian origin. The social and spatial change process of the city of Gaziantep, which has turned into a densely populated place, has accelerated. The migration of Syrian origins to Gaziantep city has led to the economic and social change of the Gaziantep urban area, causing the urban area to be dragged into the reproduction process. Migrations cause the differentiation of the space according to the usage patterns and the changes in the social and economic structure. It has been tried to evaluate the changes in the urban area caused by the Syrian refugees who migrated to the city of Gaziantep forcibly, on the data obtained as a result of survey studies, in-depth interviews and fieldwork observations. In this context, in this study, the economic and social reflections of the spatial change caused by the forced migration from Syria in the city of Gaziantep were evaluated.

1998 Adana Antlaşması’yla normalleşmeye başlayan Türkiye-Suriye ilişkileri, 2000 yılından sonra Beşar Esad’ın yönetime geçmesiyle birlikte tarihin en iyi konumuna gelmiştir. Ama “Arap baharı ya da Şam baharı” denilen süreç, Hem Türkiye-Suriye diplomasisini kesintiye uğratmış, hem de Suriye’yi iç savaşa sürüklemiştir. Sonuçta Suriyeli nüfusu başka ülkelerde sığınmacı haline getiren süreç başlamıştır. Suriyelilerin göç sürecinde en fazla tercih ettiği ülkeler arasında Türkiye ilk sırada gelmektedir. Bunun temel nedeni ise, Türkiye ile Suriye arasındaki tarihi bağların güçlü olmasından kaynaklanmaktadır. Genelde Türkiye özelde ise Gaziantep kentinin Suriyeli kaynaklı göçlerle birlikte yoğun nüfuslu mekânlara dönüşmüştür. Yoğun nüfuslu mekâna dönüşen Gaziantep kentinin, toplumsal ve mekânsal olarak değişim süreci hızlanmıştır. Gaziantep kentine yönelen Suriyeli kaynaklı göçlerin, Gaziantep kentsel alanının ekonomik ve toplumsal değişimine önayak olarak kentsel alanın yeniden üretim süreci içerisine sürüklenmesine neden olmuştur. Göçler mekânın kullanım biçimlerine göre farklılaşmasına, toplumsal ve ekonomik yapıda değişimlerin meydana gelen neden olmaktadır. Gaziantep kentine zorunlu bir şekilde göç eden Suriyeli sığınmacıların, kentsel alanda meydana getirdiği değişimleri, anket çalışmaları, derinlemesine yapılan görüşmeler ve saha çalışmasında ki gözlemler sonucunda elde edilen veriler üzerinde değerlendirilmeye çalışılmıştır. Bu kapsamda bu çalışmada, Suriye kaynaklı zorunlu göçlerin Gaziantep kentinde meydana getirmiş olduğu mekânsal değişimin, ekonomik ve toplumsal ölçekteki yansımaları değerlendirilmiştir.
SURİYELİ SIĞINMACILARIN MEKÂNI DÖNÜŞTÜRÜCÜ ETKİSİ: GAZİANTEP KENTİ ÖRNEĞİ